2020
DOI: 10.1155/2020/6675531
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior of Deep Foundation Pit under Both Overloading and Unloading Conditions

Abstract: A deep foundation pit in a station of the Hangzhou subway is adjacent to new high-rise residential buildings on the north side and to the Evergrande foundation pit being excavated on the south side. This work considers the excavation of the foundation pit in the subway station as the research subject, focuses on the difference of the deformation and Earth pressure between the north side and the south side of the foundation pit under these special working conditions through the analysis of the measured data, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
3
1
Order By: Relevance
“…e surface settlement had a typical concave profile, which corresponded to the type shown in Figure 1(b); and δ vm mainly occurred between 0.25 H e and 0.87 H e behind the wall. e measured δ vm values ranged between δ vm � 0.02% H e and δ vm � 0.13% H e , which were smaller than that those reported in the literature [6,7,10,36]. When x/H e � 0.48, δ vm increased and reached the maximum value in the region where 0 ≤ x/H e ≤ 0.48 and gradually decreased in the region where 0.48 ≤ x/H e ≤ 1.9.…”
Section: Ground Surface Settlementcontrasting
confidence: 55%
See 2 more Smart Citations
“…e surface settlement had a typical concave profile, which corresponded to the type shown in Figure 1(b); and δ vm mainly occurred between 0.25 H e and 0.87 H e behind the wall. e measured δ vm values ranged between δ vm � 0.02% H e and δ vm � 0.13% H e , which were smaller than that those reported in the literature [6,7,10,36]. When x/H e � 0.48, δ vm increased and reached the maximum value in the region where 0 ≤ x/H e ≤ 0.48 and gradually decreased in the region where 0.48 ≤ x/H e ≤ 1.9.…”
Section: Ground Surface Settlementcontrasting
confidence: 55%
“…(4) In stage 4, the second support was activated at −6.66 m. (5) In stage 5, excavation to the base −12.5 m was conducted; each layer did not exceed 3 m; and the excavation was completed in two layers. (6) In stage 6, the concrete floor was activated, and the excavation was completed.…”
Section: Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ng et al [2] described the stress paths in the soil units around the pit walls in deep foundation-pit excavation, compared and examined the eld stress paths with the laboratory stress path tests, and proposed that the mechanical behavior of many soils such as sti clay depends on their e ective-stress and stress history. Much research [3][4][5][6][7][8][9][10][11][12][13][14][15] has shown that the mechanical properties of the rocksoil body are very complex, with characteristics of nonlinearity, elastoplasticity, shear dilation, and anisotropy; the mechanical properties and failure modes not only depend on the current and nal stress state of the rock-soil body, but also are closely related to the stress history, subsequent loading direction, and the rock-soil body types; the rock-soil body may show di erent mechanical properties under different stress paths.…”
Section: Introductionmentioning
confidence: 99%